Qualitative analysis of a Mathematical model of COVID-19 with intervention strategies in the Philippines - Apdo, Rolly Najial; Paluga, Rolando Namalata (Jambura Journal of Biomathematics (JJBM), 2023)
This paper focuses on the development of a mathematical model to analyze the transmission dynamics of COVID-19 in the Philippines, where the pandemic has significantly impacted the population despite several quarantine measures, testing, contact tracing, and vaccinations. The model considers the impact of contact tracing and vaccination campaigns on disease transmission. The model is analyzed qualitatively and numerically, and the results show that increasing the contact tracing rate and vaccination rate can effectively reduce the reproduction number of the virus. The disease-free equilibrium is found to be locally asymptotically stable when the basic reproduction number is less than one, and the disease-endemic equilibrium is locally asymptotically stable when the basic reproduction number is greater than one. The study suggests that a contact tracing rate greater than 0.08847694 is required to effectively manage the transmission of COVID-19 in the target population. These findings provide insights for policymakers and public health officials in developing effective strategies to mitigate the impact of the pandemic.